Morphology and distribution of the spinner dolphin, Stenella longirostris, rough-toothed dolphin, Steno bredanensis and melon-headed whale, Peponocephala electra, from waters off the Sultanate of Oman - VAN WAEREBEEK, KOEN; GALLAGHER, MICHAEL; BALDWIN, ROBERT; PAPASTAVROU, VASSILI; Mustafa Al-Lawati, Samira (J. Cetacean Res. Manage., 1999)
The morphology of three tropical delphinids from the Sultanate of Oman and their occurrence in the Arabian Sea are presented. Body lengths of four physically mature spinner dolphins (three males) ranged from 154- l78.3cm (median 164.5cm), i.e. smaller than any known stock of spinner dolphins, except the dwarf forms from Thailand and Australia. Skulls of Oman spinner dolphins (11 = I0) were practically indistinguishable from those of eastern spinner dolphins (Stenella longirosrris orientalis) from the eastern tropical Pacific, but were considerably smaller than skulls of populations of pantropical (Stene/la longirostris longirostris) and Central American spinner dolphins (Stenella !ongirostris centroamericana). Two colour morphs (CM) were observed. The most common (CMI) has the typical tripartite pattern of the pantropical spinner dolphin. A small morph (CM2), so far seen mostly off Muscat, is characterised by a dark dorsal overlay obscuring most of the tripartite pattern and by a pinkish or white ventral field and supragenital patch. Two skulls were linked to a CMI colour morph, the others were undetermined. It is concluded that Oman spinner dolphins should be treated as a discrete population, morphologically distinct from all known spinner dolphin subspecies. Confirmed coastal range states off the Arabian Peninsula include the United Arab Emirates, the Sultanate of Oman, Yemen, Somalia, Djibouti, Saudi Arabia, Sudan and Egypt. The taxonomic position of two damaged dolphin calvariae from Oman has been the issue of much debate. This paper discusses the cranial characteristics that allow positive identification as rough-toothed dolphin (Steno bredanensis) and melon-headed whale (Peponoceplwla electro) respectively. The calvariae represent the first confirmed specimen records of these dolphin species for the Arabian Sea sensu lato.